Moving through the city : Cape Town's legacy of slavery and the performance of creolised carnival - Nsele, Zamansele (Rhodes University, Faculty of Humanities, Department of Fine Art, 2012)
After South Africa entered into democracy in 1994, a mediation period of change was set in motion. It was an invitation for South Africans to imagine and envision themselves anew (Gqola 2010). Slave memory; a neglected past, that was previously silenced came to the fore and is currently in the process of being renegotiated in post-apartheid South Africa. In the light of this, I believe that the study of the Cape Minstrel Carnival which has its social roots in slavery lends itself for an insightful interpretation within an art historical framework. While institutionally the memory of slavery was officially marginalized: comparatively, on the streets of Cape Town, the community preserved it in elusive ways embodied in the procession of Carnival through the city. This thesis explores the imagery of creolisation, through an analysis of the Cape Minstrel Carnival. Zimitri Erasmus (Erasmus 200:14) defines creolisation as cultural production that happens under the specific conditions of slavery. Before I decode some of the motifs embedded in the imagery of creolisation, in chapter one I provide an in depth analysis; of the contextual conditions of which the practice of carnival originated. My analysis is informed extensively by post-colonial theories on race, identity, and creolisation. The route of the procession of carnival reveals an alternative and clandestine history of the city of Cape Town which I believe deserves focus. In chapter two I discuss its site specificity in relation to key urban sites, such as the District Six Museum, the Slave Lodge Museum and the Bo-Kaap Museum. This thesis explores the use of performance as a corporeal tool to demarcate the city. In the process of this analysis, a repertoire of movement becomes salient in the construction of creolised identities. In chapter three I discuss the motif of the "coon" as the most salient image of creolisation in the parade; I trace its iconographic roots to the performance of blackface minstrelsy that originated from the slave plantations of the United States of America. By unpacking the racist iconography bound up in the initial construction of the "coon" , it becomes clear that its derogative meaning was subverted when it was appropriated as a symbol of celebration into the New Year's parades. As a result of its complicated history, some residents deride the parade as perpetuating racial stereotypes, by portraying "coloured" people as buffoons. Class snobbery has played a big part in the criticism. Therefore the procession of "the coons" or euphemistically the minstrels represents a cultural cringe for some and a festive celebration for others and both these sentiments coexist simultaneously. The Cape Town Minstrel Carnival can be interpreted on multiple shifting levels because it takes on an ambivalent and ambiguous position as far as meaning is concerned.
Keywords: Carnival -- South Africa -- Cape Town; Cape of Good Hope (South Africa) -- Economic conditions; Cape of Good Hope (South Africa) -- Social conditions; Cape Town -- Economic conditions; Cape Town -- Social conditions; Slavery -- South Africa -- Cape Town; Stereotypes (Social psychology -- South Africa